Brotamento de ascósporos em Colletotrichum lindemuthianum - Martins, Ana Carolina Faria (2022)
Common bean anthracnose is one of the main fungal that causes disease in crop. The disease is caused by the fungus Colletotrichum lindemuthianum, anamorphic form, which has wide variability as well as the teleomorphic (sexual) form. Sexual reproduction is the main ways of increasing genetic variability in fungi, therefore, the study of morphological traits and their sexual structures are important. The production of ascospores occurs through a meiotic cycle in homothallic strains. However, it the production of new ascospores via mitosis after this cycle, a process never observed before for the genus Colletotrichum, has recently been observed. As a result of each mitotic division, two ascospores with almond or allantoid morphology are formed. This process resembles the ascospore budding observed in fungal species of the genus Taphrina. Therefore, the objective of this work is to study and characterize the phenomenon described as budding in ascospores. In addition, the possible presence of this phenomenon in vivo in plants grown in a greenhouse was investigated. For this purpose, a strain of C. lindemuthianum called 84-1 was used. Analyses of budding process in ascopores was carried out using the fluorescent nuclear marker Propidium Iodide and images were obtained with a Fluorescence Microscope. The Ultra high resolution scanning electron microscope was also used. Cytological analysis was performed by measuring the length and width of the allantoid and almond-shaped ascospores, in addition to obtaining the percentage of budding using the inverted Zeiss Vert.A1 microscope. Two in vivo experiments were also carried out (i: plants in a greenhouse and ii: detached leaves and petioles kept in BOD) in order to evaluate the occurrence of budding. In an in vitro experiment, allantoid and almond-shaped ascospores were grown on plates with PDA medium, where the types of colonies formed were observed. Subsequently, monoascosporic cultures were obtained in order to quantify the budding percentage and the number of almond-shaped ascospores, the budding cycle was divided in six stages to better understanding. It was observed that the ascospores from post-meiotic mitosis have a nucleus with different patterns, suggesting that they are in different mitotic phases. In addition, budding occurs apically or laterally. Budding was found on detached leaves and petioles, but not on plants kept in greenhouse. significant difference was found in the length of the ascospores, with the almonds being shorter. Percentage of budding was 3%. Morphological variability was observed in colonies originating from almond-shaped and allantoid ascospores, being mostly peritetial. Finally, colonies from almond-shaped ascospores had a higher budding percentage than those from allantoid ascospores. New research should be carried out in order to better understand the biological mechanisms responsible for this phenomenon, as well as new evaluations in greenhouse and at the cytological level.